Ancylostomiasis case in a physician-dermatologist practice - E. N. Efanova; E. L. Savenko; J. E. Rusak; L. L. Fediv (Vestnik Dermatologii i Venerologii, 2017)
Hookworm disease (larva migrans) observation of a nematosis worms group is presented. Diagnosis and the treatment of a 28-year-old patient from an endemic area, who has hookworm disease, are described.